G563(P) Improving the efficient completion of electronic discharge summaries. (27th April 2015) - Cook, D; Coutinho, A; Mathew, A
Abstract : Context: Electronic discharge summaries from the general paediatric ward were audited on delay in completion and adequacy of content. Problem: Discharge summaries are essential for ensuring safe discharge from hospital. They should be completed efficiently and adequately to ensure relevant parties e.g. GPs, can follow up patients effectively. Assessment of problem and analysis of its causes: Initial audit showed 55% of discharge summaries were published within 7 days, and had many incomplete elements. It was felt omissions were due to lack of familiarity with the computer system used. By introducing new doctors to the discharge summary format, and highlighting the importance of timely discharge summaries at induction, we aimed to improve their efficient completion. Intervention: At the departmental induction, new doctos were familiarised with the discharge summary program and where to find the specific elements we aimed to improve on, highlighted by Figure 1. We emphasised the previous audit findings, and encouraged the team to be timelier. Study design: The proforma was based on the standard template of discharge summaries used on the hospital's computer system. 40 randomly selected paediatric discharge summaries were audited initially to quantify the problem. After induction, a further audit of 40 discharge summaries was conducted. Strategy for change: We aimed to improve the efficiency and completeness of discharge summaries. A rolling audit programme was implemented to compare results monthly and individuals completing the summaries were noted, enabling us to highlight problems to specific individuals if necessary. Measurement of improvement: Following the induction, 40 discharge summaries were audited. They were analysed against the predesigned proforma. Results were summarised and fed back to the paediatric team on a monthly basis, as a rolling audit, to measure ongoing improvement. Effects of changes: Results are shown in Table 1 . On re-audit 32.5% more of discharge summaries were completed within 7 days of discharge. This enables GPs to carry out requests made e.g. repeat prescriptions, thus ensuring a safer discharge process. Lessons learnt: The whole departmental staff wasn't present at the induction session; those who weren't tended to make more omissions from their summaries, and were less efficient. We shall therefore run a session at the departmental teaching, as well as at induction, as part of the rolling audit. Message for others: We audited elements of the discharged summaries we felt necessary for a smooth and safe discharge from hospital to community care. By instructing new doctors on how to use the local computer program, we improved on the efficiency and degree of completion. A rolling audit has been started and further interventions will be made.